The Implementation of ASG and SG Random Number Generators - Erkek, Esra; Tuncer, Taner (Ieee, 2013)
Linear Feedback Shift Register (LFSR) is mostly used in the implementation of Pseudo Random Number Generator (PRNG). LFSR based on PRNG techniques are used for many applications such as generating data, encryption keys and generating padding bits. Although a majority of random number generators have been implemented in software level, hardware implementation is becoming more and more popular due to the advent of faster and high density Field Programmable Gate Arrays (FPGA). In this paper, we propose implementations of FPGA Shrinking Generator (SG) and Alternating Step Generator (ASG) using LFSR based random number generation. Both systems have been implemented on Altera Cyclone IV board, and random number has been generated in the real time. Generated numbers have been tested according to National Institute of Standards and Technology (NIST) statistical test. According to the results, both SG and ASG have been shown to able to use in the cryptographic systems.
IEEE International Conference on System Science and Engineering (ICSSE) -- JUL 04-06, 2013 -- Budapest, HUNGARY
Keywords: Pseudo Random Number Generator; Shrinking Generator; Alternating Step Generator